Molecular Epidemiology of Hepatitis C Virus Infection in an Area of Hyperendemicity in Southern Italy: a Population-Based Study - Osella, Alberto R. (American Society for Microbiology, 1999)
In a cohort of subjects from Italy, anti-hepatitis C virus (HCV) and HCV RNA [HCV(+) subgroup] prevalences were 24.6 and 79.6%, respectively. HCV types 1b and 2a/c accounted for 95% of infections. Adjusted alanine aminotransferase levels were higher in males than in females and in RNA-positive subjects than in RNA-negative subjects regardless of HCV type. Genotype distribution was unrelated to demographic variables.